2019
DOI: 10.1016/j.jclepro.2019.117687
|View full text |Cite
|
Sign up to set email alerts
|

A new formulation of the electric vehicle routing problem with time windows considering concave nonlinear charging function

Abstract: The electric vehicle routing problem with time window (EVRPTW) is an extension of the traditional vehicle routing problem with time window (VRPTWs), where new features of electric vehicles are considered, such as limited battery capacities, lack of infrastructures, and long charging time. In this study, new technical formulations were presented for vehicle route selection and charging station visit, which reduces the formulation complexity without using duplicated dummy nodes or arcs. Besides, a new linearizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Extensive experiments were conducted to compare the results of directly solving the MIP models using Gurobi 7.5.0, the heuristic and exact labeling algorithm. Zuo et al (2019) focused on formulating the EVRP-NL into new MIP models that do not use duplicated dummy vertices or edges. In this work, no tailored solution procedure is given.…”
Section: Evrp With Nonlinear Charging Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive experiments were conducted to compare the results of directly solving the MIP models using Gurobi 7.5.0, the heuristic and exact labeling algorithm. Zuo et al (2019) focused on formulating the EVRP-NL into new MIP models that do not use duplicated dummy vertices or edges. In this work, no tailored solution procedure is given.…”
Section: Evrp With Nonlinear Charging Functionmentioning
confidence: 99%
“…2). Actually, the EVRPs extend the VRPs by mainly considering the following four aspects: 1) locations of the recharging (or battery swapping) stations (Yang and Sun, 2015;Schiffer and Walther, 2017;Zhang et al, 2019), 2) adoption of full or partial recharging policy (Keskin and Çatay, 2016;Sweda et al, 2017a;2017b;Macrina et al, 2019a;, 3) charging functions (Montoya et al, 2017;Froger et al, 2019;Zuo et al, 2019), and 4) multiple types of recharging stations (Felipe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Juan et al proposed the use of metaheuristics and heuristics as the most efficient way to deal with VRPs [17]. Zuo et al considered a concave, nonlinear charging function as a new energy consumption model for the EVRP [18]. Zhang et al suggested an EV battery swap station (BSS) location-routing problem with stochastic demands to determine a minimum cost scheme.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the piecewise linear approximation, the number of breakpoints is user-defined. The approximation becomes more accurate as more breakpoints are used [19].…”
Section: Optimisation Problemmentioning
confidence: 99%